Factors predicting depression among persons post-coronary artery bypass graft surgery: A cross-sectional study in Thailand - Chongopklang, Kritphummarin; Polsook, Rapin (Belitung Nursing Journal, 2024)
Background: Coronary artery bypass graft (CABG) surgery is a highly effective coronary artery disease treatment, providing immediate relief and promising long-term benefits. However, it is a major procedure with significant risks, including the potential for depression. Many patients experience depression following CABG, which can negatively impact their overall recovery, affecting both physical and mental health. Objective: This study aimed to determine factors predicting depression in patients following CABG surgery. Methods: This cross-sectional study was conducted with data collected between January and April 2024. A total of 272 post-CABG patients from two super tertiary care hospitals in Bangkok, Thailand, were recruited through purposive sampling. All research instruments were validated and tested for reliability. Data were analyzed using multiple regression analysis. Results: The study found that hope, optimism, illness perception, social support, and anxiety were correlated with depression (adjusted R² = 0.381), but these variables explained only 38.1% of the variance (p <0.05). Among these factors, anxiety (β = 0.311), optimism (β = 0.203), social support (β = -0.117), and illness perception (β = -0.143) were significant predictors (p <0.05), while hope was not a significant predictor. Thus, anxiety emerged as the most crucial predictor of depression in patients who have undergone CABG. Conclusion: Nurses play a vital role in preventing and managing depression in post-CABG patients. Screening for anxiety and addressing it can prevent depression, enhance social support, and improve outcomes. To develop effective nursing strategies, it is essential for nurses to assess anxiety and implement interventions that promote social support, optimism, and illness perception. These measures can improve care quality, reduce readmission rates, and enhance patients’ overall quality of life.